To evaluate the equation \( y = 6x + 8 - 7x - 3 \) for the values \( x = 2 \) and \( x = 6 \), follow these steps:
Step 1: Simplify the Equation
First, let's simplify the equation:
\[ y = 6x + 8 - 7x - 3 \]
Combine like terms:
\[ y = (6x - 7x) + (8 - 3) \] \[ y = -x + 5 \]
So the simplified equation is:
\[ y = -x + 5 \]
Step 2: Evaluate for \( x = 2 \)
Now plug in \( x = 2 \):
\[ y = -2 + 5 \] \[ y = 3 \]
Step 3: Evaluate for \( x = 6 \)
Now plug in \( x = 6 \):
\[ y = -6 + 5 \] \[ y = -1 \]
Summary of Results
- When \( x = 2 \), \( y = 3 \)
- When \( x = 6 \), \( y = -1 \)
Thus, the final answers are:
- For \( x = 2 \), \( y = 3 \)
- For \( x = 6 \), \( y = -1 \)